2018
DOI: 10.15414/jmbfs.2018.7.4.371-376
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Silver Nanoparticles Synthesized Using Lemongrass (Cymbopogon Citratus) Through Conventional Heating and Microwave Irradiation Approach

Abstract: Biosynthesis of nanoparticles using plant extract is an eco- friendly approach which eliminates the need for using physical and chemical techniques. Nanoparticle use in medical field specially anti-diabetes and anti-cancer application has remained in recent studies owing to its large surface area to volume ratio, which imparts them the capability to interact with any kind of membrane and enzymes in a better manner. This paper presents the optimized synthesis of silver nanoparticles (Ag NPs) using lemongrass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Biogenic SNPs have been shown to have antimicrobial,38 anticancer,39 anti-inflammatory,40 and anti-diabetic41 properties. In addition, these particles have been used to develop medicine and in various industries 42,43.…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic SNPs have been shown to have antimicrobial,38 anticancer,39 anti-inflammatory,40 and anti-diabetic41 properties. In addition, these particles have been used to develop medicine and in various industries 42,43.…”
Section: Introductionmentioning
confidence: 99%
“…Former studies reported that AgNPs can be synthesized by plants such as Cymbopogon citratus, 13 Garcinia mangostana bark extract, 14 Mucuna pruriens seed, 15 Kalanchoe pinnata leaf, 16 Acorus calamus root, 17 Chrysanthemum indicum. 11 In the current study, aqueous silver ions were reduced to AgNPs after mixing with cumin oil extract followed by incubation.…”
Section: Discussionmentioning
confidence: 99%
“…It had activity as antibacterial to Salmonella choleraesuis, Pseudomonas aeruginosa, Staphylococcus aureus [3], and Acinetobacter baumannii [4]. It also gave activity as antidiabetic [5], atherosclerosis [6], anticancer agents [7]. It's leaves also widely used as tea herbal [8].…”
Section: Introductionmentioning
confidence: 99%